On a Model for Laser Cutting involving Surface Tension. Issue 2 (2018) - Vossen, G.; Friedlich, N.A.; Hermanns, T.; Nießen, M.; Schulz, W.
Abstract: A model for laser cutting describing the movements of the two free boundaries of the melt will be presented. The model is an asymptotic approximation of a free boundary problem and involves the surface tension of the melt. The stationary solution will be given and investigated for linear stability. The results are illustrated with data from laser cutting experiments.